Economic implications of deeper South Asian-Southeast Asian integration: A CGE approach - Ganeshan Wignaraja; Peter Morgan; Michael Plummer; Fan Zhai (Asian Development Bank Institute (ADBI), 2014)
South and Southeast Asian economic integration via increased trade flows has been increasing significantly over the past 2 decades, but the level of trade continues to be relatively low. This underperformance has been due to both policy-related variables - relatively high tariff and non-tariff barriers - and high trade costs due to inefficient "hard" and "soft" infrastructure (costly transport links and problems related to trade facilitation). The goal of this study is to estimate the potential gains from South Asian-Southeast Asian economic integration using an advanced computable general equilibrium (CGE) model. The paper estimates the potential gains to be large, particularly for South Asia, assuming that the policy- and infrastructure-related variables that increase trade costs are reduced via economic cooperation and investment in connectivity. As Myanmar is a key inter-regional bridge and has recently launched ambitious, outward-oriented policy reforms, the prospects for making progress in these areas are strong. If the two regions succeed in dropping inter-regional tariffs, reducing non-tariff barriers by 50%, and decreasing South Asian-Southeast Asian trade costs by 15% - which this paper suggests is ambitious but attainable - welfare in South Asia and Southeast Asia would rise by 8.9% and 6.4% of gross domestic product, respectively, by 2030 relative to the baseline. These gains would be driven by rising exports and competitiveness, particularly for South Asia, whose exports would rise by two thirds (64% relative to the baseline). Hence, the paper concludes that improvements in connectivity would justify a high level of investment. Moreover, it supports a two-track approach to integration in South Asia, i.e., deepening intra-regional cooperation together with building links to Southeast Asia.
Keywords: C68; F12; F13; F15; F17; 330